PERAN PENDIDIK DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SMP MODERN AL-RIFAI’E 2 GONDANGLEGI MALANG - Syella Noverawati KS; Khoirul Asfiyak; Eko Nasrulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This research is a case study research on the problem of student interest in learning which focuses on: 1. The role of educators in increasing student interest in learning, 2. Difficulties in increasing student interest in learning, 3. Efforts in increasing student interest in learning. The subjects of the research were the principal, the Student Affairs section, counseling, and teachers of Al Rifa'ie 2 Modern Junior High School Gondanglegi, Malang. Methods of data collection by observation, documentation, and structured interviews. Data analysis was carried out in a qualitative descriptive manner using the case study method. The results of the study are: 1) the role of teachers in increasing student interest in learning 2) Difficulties often faced by educators in increasing student interest in learning 3) Efforts that can be made by teachers in increasing student interest in learning. Conclusion: (1) The role of educators is very important in increasing students' interest in learning. (2) The difficulties experienced by educators in increasing students' interest in learning become a challenge for educators, internal or external difficulties. (3) Efforts made by educators in increasing student interest in learning can be used as a form of problem solving in increasing interest in learning students.